2021
DOI: 10.1055/s-0040-1722605
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-Child HIV Transmission among Pregnant Women in a City with the Highest Rates of HIV in Brazil

Abstract: Objective Most of the HIV pediatric infections are acquired through mother-to-child transmission (MTCT). Porto Alegre is a state capital of Brazil that had a HIV MTCT rate of 4.1% in 2013 and the highest rate of HIV-infected pregnant women in the country during 2018. Zidovudine and nevirapine have been used in Brazil for high-risk newborns since 2012. The aim of the study was to investigate HIV MTCT rate and the factors associated with HIV transmission at a hospital that is a reference center for HIV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…HIV-1 MTCT susceptibility presents itself as a multifactorial and complex event, dependent of viral, maternal, and pediatric variables. In our study population, maternal characteristics such as low age at delivery, late diagnosis, no use of ART during pregnancy/delivery, and detectable VL in the last pregnancy trimester are associated with increased susceptibility to HIV-1 MTCT, corroborating with previous studies [ 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…HIV-1 MTCT susceptibility presents itself as a multifactorial and complex event, dependent of viral, maternal, and pediatric variables. In our study population, maternal characteristics such as low age at delivery, late diagnosis, no use of ART during pregnancy/delivery, and detectable VL in the last pregnancy trimester are associated with increased susceptibility to HIV-1 MTCT, corroborating with previous studies [ 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Younger mothers may lack experience to care for themselves and their infants, and possibly have a less favorable socioeconomic status than older women [ 31 ]. These facts can directly impact other preventive measures, leading to late diagnosis and inappropriate ART use, maximizing the transmission risks, as observed in our and other populations [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 87%
“…Antenatal HIV RNA > 1,000 copies/ml was independently associated with MTCT risk: OR (CI): 9.3 (2.6-43.1), thus complementing previous findings (49,(51)(52)(53). A Brazilian study showed an almost similar degree of risk but the only difference was most of babies were infected during the IU and not PP-MTCT as in our case study (54).…”
Section: Maternal Vl As the Predictor Of Mtctsupporting
confidence: 88%
“…28 Os dados colhidos mostram peculiaridade, não encontrada com frequência na literatura, ou seja, a associação entre o número de gestações da mulher, após o diagnóstico do HIVe a TVHIV. Estudos realizados anteriormente com a mesma população já apontavam nessa direção29 , ou seja, o número de gestações em gestante portadora do HIV, após esse diagnóstico, indicaria um risco acrescido à TVHIV.…”
unclassified